Improving Business Capacity for Online Sales: Product Photos Training for SMSEs - Niniek Imaningsih; Wirya Wardaya (Future Science, 2021)
Selling a product through an online platform has become a necessity for micro and small businesses as a strategy to respond to social distancing policy in the Covid-19 pandemic situation. Good product photos are one of the key successes of those activities. The needs analysis of the “Kartini” business group found that a poor photo technique is a major obstacle as well as a lack of equipment. Empowerment through participation with a peer teaching approach is used as a strategy to overcome those obstacles. The increase in knowledge and skill may lead “Kartini” more confidence to sell their product through an online platform.